Stabilization of Nigerian Deltaic Laterites with Saw Dust Ash. - Braide K. Honest, George Rowland Otoko & (International Journal of Scientific Research and Management (IJSRM), 2016)
Soil improvement potential of saw dust ash was studied with regards to compaction and CBR characteristicsof a deltaic laterite. The physical properties and engineering characteristics studied include the moisturecontent, Atterberg limits, compaction characteristics, CBR and unconfined compressive strength (UCS).The values of CBR obtained in the tests are within the limits recommended by the Asphalt Institute forhighway subbase and subgrade.It is concluded that saw dust ash, an industrial waste, is a cheap satisfactory stabilizing agent for subbase inlateritic fills; although its performance can be improved by combining it with other bonding materials suchas lime, and becomes an alternatives use of industrial waste to reduce the construction cost of roadparticularly in the rural areas of the country.